Experiential Metaphors in Persuasive Texts of ESOL Undergraduates - Riaz Ahmad; Dr. Muhammad Asif Gul (Social Science Review Archives, 2025)
Systemic Functional Linguistics (SFL) views Experiential Metaphors (EM) as a primary meaning making resource for creating conciseness and objectivity in formal persuasive academic prose. ESOL learners are also required to be satisfactorily proficient in the use of this advanced level linguistic tool. EM also serves as a valued linguistic choice for building a powerful argument and smooth thematic organization. Hence, we conducted the present study to explore what kinds of EMs are used by the ESOL undergraduates in Pakistan, and how frequently they use them. Working on the specially constructed corpus, NBSFs2021, from the handwritten essays on the given prompt from 81 students in BS final semester, we found that the sample population tended to show slight development in their repertoire of incongruent paradigmatic choices during their educational career. The study is significant for English for Academic Purposes (EAP) practitioners who are training their learners for attaining advanced academic writing proficiency.